Forensic analysis of MPS mtDNA data using QIAGEN biomedical genomics workbench and AQME tool – preliminary results. Issue 1 (December 2019) - Gouveia, N.; Brito, P.; Turner, B.; Lopes, V.; Bento, A.M.; Balsa, F.; Serra, A.; Sampaio, L.; Bogas, V.; Cunha, P.; Bento, M.São; Porto, M.J.
Abstract: Massively Parallel Sequencing (MPS) allows to sequence the total mitochondrial DNA (mtDNA) through specific panels. Human Mitochondria Panel is one of the QIAseq Targeted DNA panels developed by QIAGEN for MPS, which have an optimized chemistry based on the integration of unique molecular indices (UMIs). However, the major problem is the analysis of the MPS data and, therefore, it became necessary to create bioinformatics tools that would enable mtDNA analysis such as the AQME tool to be used with the QIAGEN Biomedical Genomics Workbench software. In this study, a coverage comparison workflow was tested to verify the coverage differences between two mtDNA panels, QIAseq Human Mitochondria Panel and Precision ID mtDNA Whole Genome Panel. The preliminary results showed a significant decrease in the Precision ID coverage, after the bioinformatics removal of PCR artifacts. For the QIAseq panel, this coverage variation was lower, since the UMIs enable to know more accurately the initial number of molecules in the original mtDNA sequence.